FACTORS AFFECTING PRAGMATIC TRANSFER TO FOREIGN LEARNERS - Kamsinah Kamsinah; Nurasia Natsir; Nuraziza Aliah; Ainun Fatimah (Badan Penerbit STIEPARI Press, 2022)
Pragmatic transfer is currently the subject of research by many researchers. Sociopragmatic and linguistic pragmatic factors were discovered as aspects influencing practical transfers. The aim of this study is to examine the aspects that drive the development of pragmatic transfer. This study used the discourse completion test. This required interviewing 33 of his English students and 33 of her Arabic students. This research shows that there is a psychoparagmatic dimension to how foreign language learners use and influence the language they are learning in interacting with others. By observing the psychology of the languages ​​spoken by Arabic and English students in UIN Alauddin Makassar, the mental-practical aspects that were the focus of the researcher's analysis of this study were found to be social-practical. It had the same effect as the physical aspect.